(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
Objective: The study aimed to obtain a practical evidence from the Saudi business environment, on the impact of joint auditing approach on the costs of audit performance in the Saudi business environment.Findings and Recommendations: The study findings showed a significant relation between joint auditing and the level of fixed costs for external auditing, the results also showed a significant relation between joint auditing and the level of variable costs for external auditing, furthermore the study results proved the presence of a significant relation between joint auditing and the level of conditional costs for the external auditing in Saudi context. Based on these findings, the study recommends the need to work on expanding the adoption of joint auditing, because of the many benefits that can be achieved by all the parties that are involved in the audit process, especially for its positive impact on the confidence in financial reports when compared to single firm’s auditing, and its effect on the restoration of confidence in the audit profession, and further this will be reflected on the share prices, investors’ decisions, firms’ value and advancing the economic development. The study also recommends that the related authorities and professional bodies in Saudi Arabia should work on issuing a new auditing standard for joint auditing to cover the conceptual framework for joint auditing, how it should be applied, and also the principles, procedures and mechanisms to which auditors must adhere.